Perlindungan Bagi Korban Pelecehan Seksual Dengan Pendekatan Keadilan Restoratif (Restorative Justice) - Putri Silvah Al Hikmah; Dinda Fajarohma; Hana Sabilillah (LPPM Universitas Sains dan Teknologi Komputer, 2023)
Victims of sexual harassment are common in Indonesia. Cases of sexual harassment can no longer be seen as normal cases, because victims of abuse are not only children but even adults are also victims of sexual harassment. This sexual harassment has an extraordinary impact on the victims, both psychologically, physically, economically, and even socially. As a result of this impact, the victim's condition is increasingly cornered and they experience prolonged trauma which will definitely require recovery. Therefore, there is a need for special handling of victims of sexual fraud through a Restorative Justice approach. Restorative justice as a substitute for handling criminal cases. The application of Restorative Justice can reduce intensity in correctional institutions. With efforts to approach restorative justice, can it guarantee the rights of victims as a result of sexual reduction, whether legal protection for sexual victims can be realized in realizing restorative justice. Victims will definitely experience physical and mental losses as a result of the sexual suffering they experience and later it will be difficult to heal. When viewed from a psychological side, it takes a very long time, even a lifetime. Therefore, the purpose of this research is to find out how to protect victims of sexual torture using a restorative justice approach. The research method used uses the research method in this journal using normative juridical, namely by using an approach by associating an event with the applicable laws and regulations. This was done to find a conclusion from sexual violence, restorative justice, and the resolution of cases of sexual harassment through a restorative justice approach.